2016
DOI: 10.1002/ajhb.22865
|View full text |Cite
|
Sign up to set email alerts
|

A study of the molecular variants associated with lactase persistence in different Ecuadorian ethnic groups

Abstract: The presence of the T-13910 polymorphism in the Ecuadorian population suggested that LP was a trait introduced by European migration and inherited by admixture that occurred during the colonization of South America. This variant was not fixed in a population with a history of admixture, and its allele frequency was proportional to the ancestry proportion of each Ecuadorian ethnic group. Am. J. Hum. Biol. 28:774-781, 2016. © 2016Wiley Periodicals, Inc.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 45 publications
1
9
0
Order By: Relevance
“…This is consistent with the absence of the –13910 ∗ T allele in ancient and present-day unadmixed Native Americans and with the hypothesis that this allele was probably introduced in the Americas by Europeans since the Colonial period. Furthermore, the identification of the –14011 ∗ T and –13915 ∗ G alleles in low frequencies in Afro-Brazilians from Curitiba agrees with the frequencies previously reported ( Friedrich et al, 2012b ; Paz-Y-Miño et al, 2016 ), corroborating the suggestion that the phenotypic variation observed in this study is mainly due to the –13910C > T variation of European origin.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…This is consistent with the absence of the –13910 ∗ T allele in ancient and present-day unadmixed Native Americans and with the hypothesis that this allele was probably introduced in the Americas by Europeans since the Colonial period. Furthermore, the identification of the –14011 ∗ T and –13915 ∗ G alleles in low frequencies in Afro-Brazilians from Curitiba agrees with the frequencies previously reported ( Friedrich et al, 2012b ; Paz-Y-Miño et al, 2016 ), corroborating the suggestion that the phenotypic variation observed in this study is mainly due to the –13910C > T variation of European origin.…”
Section: Discussionsupporting
confidence: 92%
“…Despite breeding these animals, there is no archeological or cultural evidence of dairy consumption by Native American populations until Europeans arrived in the late fifteenth century ( Gade, 1999 ) – cattle were not introduced in the Americas until 1493 ( Primo, 1992 ). Not surprisingly, studies regarding living Native Americans from Brazil ( Friedrich et al, 2012a ), Chile ( Fernández et al, 2016 ), Ecuador ( Paz-Y-Miño et al, 2016 ), Mexico ( Ojeda-Granados et al, 2016 ), Peru ( Figueroa et al, 1971 ), and the United States ( Duncan and Scott, 1972 ; Casey, 2005 ) identified lower LP phenotype frequencies in these populations (20% on average), suggesting that most people cannot digest lactose naturally. Countries such as Peru, Mexico, and Chile have a high proportion of Native American ancestry – 80, 57.5, and 49.3%, respectively ( Ruiz-Linares et al, 2014 ; Adhikari et al, 2016 ; Harris et al, 2018 ) – which could explain the low frequency of the LP phenotype.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent studies related the genetic factors and taste sensitivity that have characterized the populations on the perception of flavors and their choice of diet [4]. Demographically Ecuadorians have a high Native Americans ancestry.…”
Section: Introductionmentioning
confidence: 99%